The “Emotional Side” of Entrepreneurship: A Meta-Analysis of the Relation between Positive and Negative Affect and Entrepreneurial Performance - Fodor, Oana C.; Pintea, Sebastian (Frontiers in Psychology, 2017)
The experience of work in an entrepreneurial context is saturated with emotional experiences. While the literature on the relation between affect and entrepreneurial performance is growing, there was no quantitative integration of the results so far. This study addresses this gap and meta-analytically integrates the results from 17 studies (N=3810) in order to estimate the effect size for the relation between positive (PA) and negative affect (NA), on the one hand, and entrepreneurial performance (EP), on the other hand. The meta-analysis includes studies in English language, published until August 2016. The results indicate a significant positive relation between PA and EP, r=0.18. The overall NA – EP relation was not significant, r=-0.12. Only state NA has a significant negative relation with EP (r=-0.16). The moderating role of several conceptual (i.e. emotion duration, integrality etc.), sample (i.e. gender, age, education) and methodological characteristics of the studies (i.e. type of measurements etc.) are explored and implications for future research are discussed.